ثورة إقميم ظفار الُعماني 1965-1975 وموقف الجازئر وإيارن منها - محمد, سلام شريف (مجلة الدراسات المستدامة, 2023)
Keywords: Dhofar

Afterlives of Revolution: Everyday Counterhistories in Southern Oman - Wilson, Alice (Stanford University Press, 2023)
The Dhufar Revolution was fought between 1965–1976, in an attempt to depose Oman's British-backed Sultan and advance social ideals of egalitarianism and gender equality. Dhufar, the southernmost governorate in today's Sultanate, captured global attention for its revolutionaries and their liberation movement's Marxist-inspired social change. But following counterinsurgency victory, Oman's government expunged the revolution from sanctioned historical narratives. Afterlives of Revolution offers a groundbreaking study of the legacies of officially silenced revolutionaries. How do their underlying convictions survive and inspire platforms for progressive politics in the wake of disappointment, defeat, and repression?Alice Wilson considers the "social afterlives" of revolutionary values and networks. Veteran militants have used kinship and daily socializing to reproduce networks of social egalitarianism and commemorate the revolution in unofficial ways. These afterlives revise conventional wartime and postwar histories. They highlight lasting engagement with revolutionary values, the agency of former militants in postwar modernization, and the limitations of government patronage for eliciting conformity. Recognizing that those typically depicted as coopted can still reproduce counterhegemonic values, this book considers a condition all too common across Southwest Asia and North Africa: the experience of defeated revolutionaries living under the authoritarian state they once contested.
Keywords: Dhofar